TRANSLATION ISSUES OF PHRASEOLOGICAL UNITS IN THE ENGLISH LANGUAGE - Nasirdinov Oybek Abdubannonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Language and translation are main parts of humans’ life today. So several translational methods have been researched for many years and some issues are still occurred in translational process. The aim of this article is to illustrate some problems of translation of phrasal verb from English into Uzbek